'Believers in Biology': A Co-ordinated Effort to Disrupt the 2022 Census. Issue 1 (February 2023) - Pedersen, Sarah
Abstract : This article investigates the attempt by some gender-critical Scots, led by organisations such as For Women Scotland, to disrupt the administration of the 2022 census in Scotland. They used their census returns to register a protest around guidance relating to the Sex question and around the wider issue of the Scottish Government's plans to reform the Gender Recognition Act. Protestors used social media to share images of their protest on the census forms over the whole census period, meaning that potential protesters were more likely to choose to protest because they saw a growing number of others sharing what they had done. It is suggested that this protest has contributed, and will continue to contribute, to costs relating to the administration of the census and the processing of census data, including the production and administration of paper census forms; the extension of the deadline for completion of the census; and the ability to use machines to read and process the data. Their action was linked by many protesters to the actions of the suffragettes in relation to the 1911 census, with the expectation that their protests would be visible in 100 years' time. However, data-protection policies mean many of their actions will not be recorded.